The effect of orthokeratology lenses on optical quality and visual function in children - Lu, Weiwei; Song, Guanxin; Zhang, Yuhan; Lian, Yan; Ma, Ke; Lu, Qingqing; Jin, Yiyu; Zhao, Yang; Zhang, Shuyu; Lv, Fan; Jin, Wanqing (Frontiers in Neuroscience, 2023)
Purpose To assess changes in optical quality and visual function in children after 3 months of wearing orthokeratology (OK) lenses. Methods A total of 25 myopic children aged 8–12 years were recruited and completed the follow-up study. Optical quality, visual function and corneal morphology were assessed at baseline and at follow-ups 1 and 3 months after wearing OK lenses. Optical quality parameters mainly included the modulation transfer function (MTF) cutoff, objective scattering index (OSI), Strehl ratio (SR) and the predicted visual acuities (PVAs). Visual function was assessed by visual acuity, monocular contrast sensitivity function (CSF) across five spatial frequencies and the area under the log contrast sensitivity function (AULCSF) that was also computed as an index for overall CSF. Results The MTF cutoff and SR values both increased after 1 month of wearing the OK lenses (baseline vs. 1 month: PMTF = 0.008 and PSR = 0.049); this improvement plateaued after 3 months of lens wear (1 month vs. 3 months: PMTF = 0.626, PSR = 0.428). The corneal morphology also showed the similar change trend. The OSI showed the opposite change trend (baseline vs. 1 month: POSI < 0.001; 1 month vs. 3 months: POSI = 0.720). The mean CSF at 1.5 cpd decreased significantly after 1 month of wearing the lenses (baseline vs. 1 month: p = 0.001) and recovered after 3 months of lens wear (baseline vs. 3 months: p = 0.076). CSF at spatial frequencies of 3, 6, 12 and 18 cpd as well as the AULCSF did not significantly differ between any two timepoints (all Ps > 0.05). Conclusion After 3 months of wearing OK lenses, the subjects exhibited a decrease in optical quality, similar to corneal morphology, whereas their visual function remained largely unchanged. Thus, the optical quality was more susceptible to OK lenses than visual function in children. The initial month of OK treatment of children is a key period to be paid close attention to deterioration of optical quality and visual function.